The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1016/j.radi.2021.04.008
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the Covid-19 pandemic on the mental health and work morale of radiographers within a conventional X-ray department

Abstract: Introduction: There is a plethora of literature that has described the negative impact of the COVID-19 pandemic on the mental health of healthcare staff worldwide. Our aim was to investigate the physical and mental demands of mobile x-ray imaging on radiographers during the first wave of the COVID-19 pandemic, within a local NHS Trust. Methods: A total of 16 participants from 1 NHS Trust took part within this study. Both quantitative and qualitative data was obtained through an online survey. Statistical data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 41 publications
1
14
0
2
Order By: Relevance
“…54e56 The healthcare workforce has to balance strict measures to protect both patients, colleagues, and the general public from contracting COVID-19, while not compromising on the access, availability and quality of healthcare service. 57,58,65,67 These demands have placed a toll on the healthcare workforce worldwide.…”
Section: Theme 3: Workforce Mental Health and Well-beingmentioning
confidence: 99%
“…54e56 The healthcare workforce has to balance strict measures to protect both patients, colleagues, and the general public from contracting COVID-19, while not compromising on the access, availability and quality of healthcare service. 57,58,65,67 These demands have placed a toll on the healthcare workforce worldwide.…”
Section: Theme 3: Workforce Mental Health and Well-beingmentioning
confidence: 99%
“…The media contributed to increase anxiety among people. Yasin et al (2021) argue that the media have contributed to raise the state of anxiety that workers in the health sector face. This indicates that both traditional and social media can generate anxiety, stress and depression (Holmes et al, 2020;Rubin and Wessely, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The media contributed to increase anxiety among people. Yasin et al. (2021) argue that the media have contributed to raise the state of anxiety that workers in the health sector face.…”
Section: Introductionmentioning
confidence: 99%
“…One example of this was the continuously changing guidance regarding PPE in the initial stage of the pandemic, which increased fear and anxiety levels for radiographers. 5,30 At this time, managers often had to make unpopular decisions regarding restructuring of services which had a significant impact on staff morale. 3,31 Managers felt that staff trust in their ability to lead was deeply impacted by both of these phenomena.…”
Section: Discussionmentioning
confidence: 99%
“…37 However, since the pandemic, studies have indicated mixed findings with regard to healthcare professionals (including radiographers) accessing support services noting some reluctance still to utilise the more 'stigmatised' mental health services. 30,38,39 It is possible that managers are unaware of the extent to which their staff utilise these services and therefore underestimate their importance to their staff. Local audits of support services accessed by radiographers should be undertaken regularly to explore which support services are being accessed most frequently and considered most beneficial to radiographers to ensure optimal uptake of these services.…”
Section: Discussionmentioning
confidence: 99%